Zooplankton Composition in Super-Intensive Whiteleg Shrimp, Litopenaeus vannamei (Boone, 1931) Culture Tanks - Lien Nguyen; Tu Phan; Son Vu; Diep Doan (Bogor Agricultural University, Indonesia, 2022)
This study aimed to determine the zooplankton species composition in super-intensive whiteleg shrimp, Litopenaeus vannamei (Boone, 1931) tanks. The research was conducted from January to May 2021 in Bac Lieu City, Bac Lieu province, Vietnam. Eleven sampling times were divided into two periods, the nursery phase (six times) and the grow-out phase (five times) of shrimp culture. The results showed that water quality parameters fluctuated dramatically during the culture period, in which some nutrient concentrations tended to increase at the end of the shrimp culture period. Nine zooplankton species were recorded, of which five species belonged to Protozoa, three Rotifera species, and one Copepoda species. The number of zooplankton species did not differ significantly among the sampling periods. Protozoa had the highest species composition and density during most of the shrimp culture period. Copepoda was only identified in the nursery stage of shrimp culture. The species component of zooplankton had a close positive correlation with temperature, but their abundance did not have a significant relationship with water quality parameters because each species was affected by the different water quality parameters. Zoothamnium sp. had significantly positive correlations with total ammonia nitrogen (TAN), nitrate (NO3)-, total phosphorus (TP), and total nitrogen (TN) concentrations. The rotifer Brachionus plicatilis had a strong relationship with TP content, whereas Dartintinnus alderae had a strong relationship with alkalinity. Protozoa dominance in shrimp tanks could affect shrimp growth, decreasing the economic efficiency of shrimp farming. Therefore, the results of this study contribute to water quality and natural food management to improve shrimp productivity.